A Series of Ferulic Acid Amides Reveals Unexpected Peroxiredoxin 1 Inhibitory Activity with in vivo Antidiabetic and Hypolipidemic Effects. (29th October 2020) - Yasmin, Sabina; Cerchia, Carmen; Badavath, Vishnu Nayak; Laghezza, Antonio; Dal Piaz, Fabrizio; Mondal, Susanta K.; Atlı, Özlem; Baysal, Merve; Vadivelan, Sankaran; Shankar, S.; Siddique, Mohd Usman Mohd; Pattnaik, Ashok Kumar; et al.
Abstract: Insulin resistance is a major pathophysiological feature in the development of type 2 diabetes (T2DM). Ferulic acid is known for attenuating the insulin resistance and reducing the blood glucose in T2DM rats. In this work, we designed and synthesized a library of new ferulic acid amides (FAA), which could be considered as ring opening derivatives of the antidiabetic PPARγ agonists Thiazolidinediones (TZDs). However, since these compounds displayed weak PPAR transactivation capacity, we employed a proteomics approach to unravel their molecular target(s) and identified the peroxiredoxin 1 (PRDX1) as a direct binding target of FAAs. Interestingly, PRDX1, a protein with antioxidant and chaperone activity, has been implied in the development of T2DM by inducing hepatic insulin resistance. SPR, mass spectrometry‐based studies, docking experiments and in vitro inhibition assay confirmed that compounds VIe and VIf bound PRDX1 and induced a dose‐dependent inhibition. Furthermore, VIe and VIf significantly improved hyperglycemia and hyperlipidemia in streptozotocin‐nicotinamide (STZ‐NA)‐induced diabetic rats as confirmed by histopathological examinations. These results provide guidance for developing the current FAAs as new potential antidiabetic agents. Abstract : Attenuating insulin resistance : Ferulic acid derivatives (FAAs) VIe and VIf displayed inhibitory activity against peroxiredoxin 1 (PRDX1), an antioxidant protein implied in the development of T2DM. VIe and VIf improved hyperglycemia and hyperlipidemia in STZ‐NA‐induced diabetic rats, preserved the normal histological appearance of liver and recuperated the structural integrity of pancreatic islet β‐cells and tissues. Therefore, FAAs represent new promising antidiabetic agents.